Advances in Molecular Mechanisms and Treatment of Radiation-Induced Pulmonary Fibrosis - Chen, Zhongjie; Wu, Zhiqiang; Ning, Wen (Translational oncology, 2019)
Radiation-induced pulmonary fibrosis (RIPF) is a common complication in patients with lung cancer and breast cancer after receiving thoracic radiotherapy. The average incidence of RIPF is 16%-28% after radiotherapy. RIPF includes a heterogeneous group of lung disorders characterized by progressive and irreversible destruction of lung architecture and disruption of gas exchange. The clinical signs of RIPF include increasing dyspnea, deteriorating lung function, and accumulation of interstitial fluid, eventually leading to respiratory failure. No medical therapy for RIPF has been approved for routine clinical use despite the apparent need for an effective treatment. Numerous signaling pathways are involved in the initiation and progression of RIPF. Also, various approaches for RIPF treatments have focused on several aspects of the current understanding of the molecular pathology of RIPF. This review used the mechanistic categories of associated cell signaling pathways, epithelial cell dysfunction and senescence, abnormal lung remodeling, and aberrant innate and adaptive immunity to review the published literature on RIPF to date and then to identify potential areas for the effective treatment of RIPF.